PENGARUH ATTRIBUTES RELATED TO PRODUCT, SERVICE DAN PURCHASE TERHADAP KESETIAAN MEREK (STUDI KASUS PERGURUAN TINGGI DI KOTA BEKASI) - Hendrayanti, Endang; Rafiq, Muhammad (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
The aim of this research is to seethe influence of satisfaction-former to loyalty. The research method is descriptive-conclusive research. Multiple regression model is used to analysis the influence of attributes related to: product, servicef dan purchase to the brand loyalty. The result indicate that satisfaction have an big effect to loyalty. The satisfaction to the college influenced by attributes of related to courtesy, attention, consideration, sociability, ability of communications, amenity get information, reputation and interest Satisfaction will be reach by student when they can see and prove that college which their select really can print certifiable collegiate and accepted everywhere. After this, the student by itself will lick lips and become very loyal to college which their choose.